Penanaman Karakter Toleran Melalui Projek Penguatan Profil Pelajar Pancasila (P5) - Astuti, Tri Marhaeni Pudji; Setyowati, Dewi Liesnoor; Hidayah, Isti; Kusumandari, Rafika Bayu; Fajar, Fajar; Setyoko, Didik Tri (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2024)
Intolerance towards aspects of ethnicity, religion, politics, economy, culture, and so on can trigger the vulnerability of national life. The Merdeka Curriculum through the Pancasila Student Profile Strengthening Project (P5) is a new strategy in instilling national doctrine. This article analyses the implementation of P5 to strengthen tolerant character through the theme of bhineka tunggal ika and democratic voice, based on the results of field research conducted at SMP Negeri 1 Kandangan and SMPN 2 Temanggung. This research uses a qualitative approach. Data were collected using interviews, observations, FGDs, and documentation studies. Data analysis using interactive descriptive techniques. Research findings: 1) the theme of democratic voice through speeches and debates to develop speaking skills and respect for differences in views and opinions; 2) the theme of bhineka tunggal ika making clippings, stories on the mading, drama narratives and acting out story narratives, and making drama performance videos. P5 is a vehicle for learners to develop various competencies and tolerant characters that are crucial for strengthening the social resilience of society and supporting national integration.